2018
DOI: 10.1186/s13287-018-0872-7
|View full text |Cite
|
Sign up to set email alerts
|

Acidic preconditioning of endothelial colony-forming cells (ECFC) promote vasculogenesis under proinflammatory and high glucose conditions in vitro and in vivo

Abstract: BackgroundWe have previously demonstrated that acidic preconditioning of human endothelial colony-forming cells (ECFC) increased proliferation, migration, and tubulogenesis in vitro, and increased their regenerative potential in a murine model of hind limb ischemia without baseline disease. We now analyze whether this strategy is also effective under adverse conditions for vasculogenesis, such as the presence of ischemia-related toxic molecules or diabetes, one of the main target diseases for cell therapy due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…However, in combination with the chemoattractant stimulus fMLP, both inflammatory cellular responses were synergistically increased in the presence of glucose (Oldenborg and Sehlin, 1999). In addition, a previous work published by our group has demonstrated that inhibition of in vitro angiogenic responses (including endothelial proliferation, migration, survival and tubule formation) induced by TNF-α is increased in combination with glucose (Mena et al, 2018). These results suggest that glucose synergizes with other stimuli to enhance proinflammatory and anti-angiogenic responses.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…However, in combination with the chemoattractant stimulus fMLP, both inflammatory cellular responses were synergistically increased in the presence of glucose (Oldenborg and Sehlin, 1999). In addition, a previous work published by our group has demonstrated that inhibition of in vitro angiogenic responses (including endothelial proliferation, migration, survival and tubule formation) induced by TNF-α is increased in combination with glucose (Mena et al, 2018). These results suggest that glucose synergizes with other stimuli to enhance proinflammatory and anti-angiogenic responses.…”
Section: Discussionsupporting
confidence: 56%
“…Human microvascular endothelial cells (HMEC-1) were grown in MCDB-131 supplemented with fetal bovine serum (FBS) (10%), L-glutamine (10 mM) and streptomycin (100 µg/mL), penicillin (100 U/mL), EGF (10 ng/mL), and hydrocortisone (1 µg/mL) at 37 • C in a humidified 5% CO 2 incubator (Etulain et al, 2018). Human umbilical vein endothelial cells (HUVEC) were obtained from four different donors as previously described (Mena et al, 2018) and were expanded and maintained in Endothelial Growth Medium 2 (EGM2; Lonza, Walkersville, MD, United States) containing Endothelial Basal Medium 2 (EBM2) supplemented with FBS, hydrocortisone, human fibroblast growth factor (hFGF), VEGF, human long R3, insulin-like growth factor-1 (R3-IGF-1), ascorbic acid, human epidermal growth factor (hEGF), gentamicin, amphotericin-B and heparin (Mena et al, 2014). After washing, growth factor-enriched medium was totally replaced by PRPr.…”
Section: In Vitro Endothelial Proliferation and 2d-migration Assaysmentioning
confidence: 99%
“…Fourth, ECFCs’ angiogenic activity could be further reduced by the harsh microenvironment of ischemic tissues. For instance, ECFC proliferation and tube formation are affected in the presence of elevated pro-inflammatory signaling [ 129 ], oxidative stress [ 130 ], hypoxia [ 131 , 132 ], and damage-associated molecular patterns (DAMP), such as extracellular histones [ 133 ] and monosodium urate [ 109 ].…”
Section: Manipulation Of Pro-angiogenic Signaling Pathways To Imprmentioning
confidence: 99%
“…Consistently, a human platelet lysate gel has been recently designed to provide a 2D matrix enriched with growth factors and able to promote ECFC amplification and networking formation [ 141 ]. Likewise, ex vivo proliferation is enhanced by pre-conditioning ECFCs with the pro-angiogenic cues fucoidan [ 142 , 143 , 144 ] and SDF-1α [ 145 , 146 ], with the hexapeptide SFLLRN, which mimics the thrombin effect on PAR-1 [ 53 , 147 , 148 ], with the erythroid growth factor EPO [ 78 , 106 , 149 , 150 , 151 , 152 ], with the isoflavone genistein [ 153 , 154 ], with nicotine [ 155 ], and with an acidic growth medium [ 129 , 156 ]. Hypoxic pre-conditioning has also been proposed as an alternative approach to accelerate the ex vivo expansion of primary ECFCs [ 157 , 158 ], although subsequent studies demonstrated that their angiogenic activity is compromised under hypoxia [ 131 , 132 ].…”
Section: Manipulation Of Pro-angiogenic Signaling Pathways To Imprmentioning
confidence: 99%
See 1 more Smart Citation